FLYPAPER EFFECT PADA PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP ALOKASI BELANJA DAERAH PEMERINTAH KOTA SURAKARTA TAHUN 2013 – 2017 - Kevin Firnandyas Nusa Pradana; Suharno Suharno; Bambang Widarno (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of PAD and DAU on regional spending and determine whether there is a flypaper effect on PAD and DAU. This research was conducted at the local government of Surakarta City. The type of data used is quantitative data. The data source used is secondary data. Data collection techniques in this study using documentation. Data analysis techniques using multiple linear analysis and flypaper effect test. The results of this study indicate partially the PAD significance value of 0.037 <0.05, the PAD has a significant effect on the regional expenditure allocation. The significance value of the DAU is 0.062 > 0.05, so the DAU has no significant effect on the allocation of regional expenditure. PAD and DAU simultaneously have a significant effect on regional expenditure allocations with a significance value of 0.006 <0.05. The PAD coefficient value is 1.032 and the DAU coefficient value is 0.887. There was no flypaper effect on the Surakarta city government finances in 2013 - 2017, because the PAD coefficient value was greater than the DAU coefficient value.